Global Analysis of Plasma Lipids Identifies Liver-Derived Acylcarnitines as a Fuel Source for Brown Fat Thermogenesis - Simcox, Judith; Geoghegan, Gisela; Maschek, John Alan; Bensard, Claire L.; Pasquali, Marzia; Miao, Ren; Lee, Sanghoon; Jiang, Lei; Huck, Ian; Kershaw, Erin E.; Donato, Anthony J.; Apte, Udayan; et al. (Cell metabolism, 2017)
Cold-induced thermogenesis is an energy-demanding process that protects endotherms against a reduction in ambient temperature. Using non-targeted liquid chromatography-mass spectrometry-based lipidomics, we identified elevated levels of plasma acylcarnitines in response to the cold. We found that the liver undergoes a metabolic switch to provide fuel for brown fat thermogenesis by producing acylcarnitines. Cold stimulates white adipocytes to release free fatty acids that activate the nuclear receptor HNF4α, which is required for acylcarnitine production in the liver and adaptive thermogenesis. Once in circulation, acylcarnitines are transported to brown adipose tissue, while uptake into white adipose tissue and liver is blocked. Finally, a bolus of L-carnitine or palmitoylcarnitine rescues the cold sensitivity seen with aging. Our data highlight an elegant mechanism whereby white adipose tissue provides long-chain fatty acids for hepatic carnitilation to generate plasma acylcarnitines as a fuel source for peripheral tissues in mice. [Display omitted] •Increase in plasma acylcarnitines is required for adaptive thermogenesis•Adipose tissue lipolysis promotes hepatic acylcarnitine production•HNF4α stimulates expression of genes involved in acylcarnitine metabolism•Brown adipocytes increase uptake of acylcarnitines in response to the cold Simcox et al. identify acylcarnitines as a novel source of energy for brown fat thermogenesis in mice and show that in response to cold, the liver activates a transcriptional program through HNF4α to increase acylcarnitine production. Blocking hepatic acylcarnitine synthesis impairs adaptive thermogenesis.